2007
DOI: 10.2105/ajph.2006.086470
|View full text |Cite
|
Sign up to set email alerts
|

Effective Lay Health Worker Outreach and Media-Based Education for Promoting Cervical Cancer Screening Among Vietnamese American Women

Abstract: Combined intervention motivated more Vietnamese American women to obtain their first Pap tests and to become up-to-date than did media education alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
164
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(176 citation statements)
references
References 28 publications
2
164
2
8
Order By: Relevance
“…23 Mock found increases in the rate of screening for cervical cancer for Vietnamese women in both intervention and control groups (intervention 65.8 % to 81.8 %, p<0.001; control 70.1 % to 75.5 %, p<0.001). 22 The increase in the intervention group was significantly greater than that in the control (Z test p= 0.001). 22 Fernandez found that 39.5 % of Latinas in the intervention group completed screening compared to 23.6 % in the control group (p<0.05).…”
Section: Impact Of Interventions To Increase Screeningmentioning
confidence: 87%
See 4 more Smart Citations
“…23 Mock found increases in the rate of screening for cervical cancer for Vietnamese women in both intervention and control groups (intervention 65.8 % to 81.8 %, p<0.001; control 70.1 % to 75.5 %, p<0.001). 22 The increase in the intervention group was significantly greater than that in the control (Z test p= 0.001). 22 Fernandez found that 39.5 % of Latinas in the intervention group completed screening compared to 23.6 % in the control group (p<0.05).…”
Section: Impact Of Interventions To Increase Screeningmentioning
confidence: 87%
“…Of the studies that evaluated the impact of multiple interventions, five included education delivered by lay health workers plus navigation in combination with other interventions (educational materials and/or messages in the media), on the rate of screening for cervical cancer. 15,22,23,35,36 Compared to control, all found an increase in the rate of screening for cervical cancer with the intervention. Wang found a 70 % rate of screening for cervical cancer with the intervention for Chinese American women compared to 11.1 % for the control condition (p<0.001).…”
Section: Impact Of Interventions To Increase Screeningmentioning
confidence: 91%
See 3 more Smart Citations